Priority and Prospect of Sulfide‐Based Solid‐Electrolyte Membrane - Liu, Hong; Liang, Yuhao; Wang, Chao; Li, Dabing; Yan, Xiaoqin; Nan, Ce‐Wen; Fan, Li‐Zhen (Advanced materials (Weinheim), 2023)
All‐solid‐state lithium batteries (ASSLBs) employing sulfide solid electrolytes (SEs) promise sustainable energy storage systems with energy‐dense integration and critical intrinsic safety, yet they still require cost‐effective manufacturing and the integration of thin membrane‐based SE separators into large‐format cells to achieve scalable deployment. This review, based on an overview of sulfide SE materials, is expounded on why implementing a thin membrane‐based separator is the priority for mass production of ASSLBs and critical criteria for capturing a high‐quality thin sulfide SE membrane are identified. Moreover, from the aspects of material availability, membrane processing, and cell integration, the major challenges and associated strategies are described to meet these criteria throughout the whole manufacturing chain to provide a realistic assessment of the current status of sulfide SE membranes. Finally, future directions and prospects for scalable and manufacturable sulfide SE membranes for ASSLBs are presented. This review expounds on why implementing a membrane‐based electrolyte is the priority for mass production of all‐solid‐state lithium batteries and identifies critical criteria for capturing a high‐quality thin sulfide electrolyte membrane. The challenges and associated strategies for achieving these criteria in terms of material availability, membrane processing, and cell integration are systematically analyzed and summarized.